Age and Psychological Well-being as Predictors of Male Child Parenting among Married Adults - Ramata Funsho Sanni; Adekola Kamil Lasisi; Taiye Hassan Ahmed (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Age is a critical factor in parenting, as parenting styles and attitudes can vary significantly across different age groups. Psychological well-being encompasses an individual's emotional health, life satisfaction, and overall mental state. The study examined age and psychological well-being as predictors of Male Child Parenting among married adults in Kwara State. A descriptive survey was used. The study was conducted on 384 married adults in Kwara Central Senatorial District, Kwara State, using a self-designed questionnaire called